(untitled) - FAO (Rome, 1999)
The FAO Yearbook of Fishery Statistics: Commodites is a compitation of annual statistical data on production and foreign trade of fisery commodities for all countries and territories of the world. The Yearbook includes data series on production of processed and preserved fishery products in terms of quantity and value. It also gives statistics of apparent consumption of fish and fishery products, the value of world catches and their disposition. Statistical information in the Yearbook is based primarily on data provided by the countires through questionnaries or official publications.
Keywords: fisheries - catch effort,fisheries - fishing effort,fisheries - research,fisheries - statistics - 1999